Fatty acid profile of Albizia lebbeck and Albizia saman seed oils: Presence of coronaric acid - Knothe, Gerhard (Animo Repository, 2015)
In this work, the fatty acid profiles of the seed oils of Albizia lebbeck and Albizia saman (Samanea saman) are reported. The oils were analyzed by GC, GC-MS and NMR. The most prominent fatty acid in both oils is linoleic acid (30-40%), followed by palmitic acid and oleic acid for A. lebbeck and oleic acid and behenic acid for A. saman. Both oils contain slightly more than 30% saturated fatty acids with stearic, eicosanoic and tetracosanoic acids present as well as odd-numbered saturated fatty acids in minor amounts. Furthermore, for the first time, epoxy fatty acids are reported in the fatty acid profiles of Albizia seed oils. Coronaric acid (9,10-epoxy-12(Z)-octadecenoic acid) is the major epoxy fatty acid at approximately 3-4% of the fatty acid profiles with minor amounts of vernolic (12,13-epoxy-9(Z)-octadecenoic acid) and 9,10-epoxystearic acids also detected. The results are compared to previous literature on the fatty acid profiles of other Albizia seed oils. The coronaric acid content of Albizia resembles that of Acacia species with both genera belonging to the Fabaceae family. The mass spectrum of the pyridylcarbinol (picolinyl) ester of coronaric acid is reported. © 2014 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.